3D intermetallic anodes for Lithium-ion batteries - Murat, E.; Adi, A.; Bakenov, Z.; Nurpeissova A. (My University, 2018)
Abstract Recently various three-dimensional (3D) battery architectures have emerged as a new direction for powering microelectromechanical systems and other small autonomous devices. The ultimate goal of such unique battery architecture is to obtain a high surface area substrate coated with thin layers of anode, electrolyte and cathode materials to enhance the energy density per foot print area, while maintaining a large power density. In view of this, attempts on formulating 3D structured anode utilizing widely available three dimensional mesoporous nickel foam and tin alloy matrix are reported